New immunoassays for total, IgA and IgM antibodies against hepatitis E virus: Prevalence in Italian blood donors and patients with chronic liver or kidney diseases. Issue 5 (May 2016) - Ricco, Gabriele; Bonino, Ferruccio; Lanza, Maria; Scatena, Fabrizio; Alfieri, Carlo M.; Messa, Piergiorgio; Marchisio, Edoardo; Mascolo, Giovanni; Romanò, Luisa; Galli, Cristina; Li, Tian-Cheng; Wakita, Takaji; et al.
Abstract: Background: Hepatitis E virus (HEV) is a zoonotic agent that causes acute hepatitis in humans with sporadic infections and outbreaks in developing countries worldwide. The global spread of HEV remains underestimated because of subclinical infections and lack of sensitive diagnostic assays. Aims: To study the prevalence of HEV antibodies (anti-HEV) in sera of blood-donors and patients with chronic-liver-disease and chronic-renal-disease, using newly developed anti-HEV assays. Methods: 396 sera from 199 blood-donors, 109 chronic-liver-disease patients and 88 chronic-renal-disease patients and three standard reference serum panels were tested in parallel with a sensitive reference anti-HEV assay and newly developed assays for IgA, IgM and total anti-HEV based on HEV-like-particles produced by recombinant baculo-viruses. Results: Overall, total anti-HEV was detected in 12.9% (7.0% blood-donors, 9.2% and 30.7% chronic-liver-disease patients and chronic-renal-disease patients, respectively). We observed a higher anti-HEV prevalence in older subjects and in chronic-renal-disease patients in relation with degree on immune-depression ( p  < 0.001). Results from reference serum panels showed an optimal and slightly better performance of the new assay over the commercially available assay. Conclusions: Newly developed anti-HEV assays using recombinant HEV-like-particles showed optimal diagnostic performances assessing that HEV-infection is endemic in Italy with seroprevalence ranging from 7% to 30% in blood donors and immune-compromised hosts, respectively.